Perencanaan Sistem Instalasi Pengolahan Air Limbah Komunal di Perumahan Grand Ville Taba Lestari Kota Lubuklinggau Provinsi Sumatera Selatan - Okma Yendri; Herpi Deska Ardinata (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2020)
The purpose of this research are to plan, design and estimate the construction cost of a communal wastewater treatment system in the Grand Ville Taba Lestari housing town of Lubuklinggau. The domestic wastewater, comes from businesses, residential activities, restaurants, offices, apartments and dormitories. The wastewater distribution system for residential area uses a shallow sewer system, namely domestic wastewater from sanitary ware (latrines, sinks, floor drain, kitchen sink, etc.) directly connected using a wastewater pipe and the wastewater distribution system in this design, uses a gravity system. Communal wastewater treatment plant is expected to prevent and reduce the occurrence of environmental pollution. From the site-plan, the maximum number of occupant are 369 persons, resulting in a wastewater debit of 40.51 m3/day. The designed dimensions of the wastewater treatment plant are based on the amount of wastewater produced, which is 9.5 m long, 3 m wide with a depth of 2 m. Piping network are 475.50 m of parcel pipe, 478.93 m of service pipe, 434.6 m of lateral pipe and 3 m of main pipe. The cost required for constructing the communal wastewater treatment plant in the Grand Ville Taba Lestari Housing is Rp. 335,500,000.00.-.